A germline JAK2 exon12 mutation and a late somatic CALR mutation in a patient with essential thrombocythemia - Hao, Zhuanghui; Li, Juan; Gao, Feng; Ren, Weixiao; Lu, Xiaomei; Feng, Jinyi; Zhang, Chen; Bian, Sicheng; Xie, Juan; Luo, Ming; Chang, Jianmei; Yang, Wanfang; et al. (Frontiers in Oncology, 2024)
It has been discovered that Janus kinase 2 (JAK2) exon12 mutations lead to the polycythemia vera (PV) phenotype, while somatic mutations of calreticulin (CALR) are associated with essential thrombocythemia (ET) or primary myelofibrosis. In this article, we report a case of ET with coexistence of JAK2 exon12 and CALR mutations. The objective of this study was to elucidate the pathogenicity mechanism of a JAK2 exon12 mutation (JAK2N533S) and the role of the coexistence of mutations on the hematological phenotype.Three distinct tumor subclones, namely JAK2N533S het+ /CALRtype1 het+ , JAK2N533S het+ /CALR wt , and JAK2N533S het+ /CALRtype1 hom+ , were identified from erythroid and granulocyte colonies. The analysis of hair follicles yielded positive results for JAK2N533S. According to the bioinformatics analysis, JAK2N533S may exert a minor effect on protein function. Functional studies showed that JAK2N533S did not have a significant effect on the proliferation of Ba/F3 cells, similar to wild-type JAK2. Notably, there were no increased phosphorylation levels of JAK2-downstream signaling proteins, including STAT3 and STAT5, in Ba/F3 cells harboring the JAK2N533S.Our study revealed that the JAK2N533S het+ /CALRtype1 het+ subclone was linked 3 to a significant expansion advantage in this patient, indicating that it may contribute to the development of the ET phenotype. We further demonstrated that JAK2N533S, as a noncanonical JAK2 exon12 mutation, is a germline mutation that may not exert an effect on cell proliferation and protein function. These results imply that certain noncanonical JAK2 mutations are not gain-of-function mutations leading to the development of myeloproliferative neoplasms.